2019
DOI: 10.1177/2192568219831687
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Radiation and Lowering Costs With a Standardized Care Pathway for Nonoperative Thoracolumbar Fractures

Abstract: Study Design:Retrospective observational study.Objective:There is marked variation in the management of nonoperative thoracolumbar (TL) compression and burst fractures. This was a quality improvement study designed to establish a standardized care pathway for TL fractures treated with bracing, and to then evaluate differences in radiographs, length of stay (LOS), and cost before and after the pathway.Methods:A standardized pathway was established for management of nonoperative TL burst and compression fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…After each position change, check whether the pipeline is unobstructed, and check whether the circuit is smooth and whether the electrode is pasted to avoid the pressure. When adjusting the head, support the lower jaw and the forehead, avoid supporting the face from both sides, and prevent the face from being stretched too tight when it is lifted, which increases the chance of damage (Gumussuyu et al, 2019;Hanson et al, 2019). In addition, for female patients, their breasts should be placed inside the prone frame to reduce breast compression, and male patients should avoid penile compression.…”
Section: Discussionmentioning
confidence: 99%
“…After each position change, check whether the pipeline is unobstructed, and check whether the circuit is smooth and whether the electrode is pasted to avoid the pressure. When adjusting the head, support the lower jaw and the forehead, avoid supporting the face from both sides, and prevent the face from being stretched too tight when it is lifted, which increases the chance of damage (Gumussuyu et al, 2019;Hanson et al, 2019). In addition, for female patients, their breasts should be placed inside the prone frame to reduce breast compression, and male patients should avoid penile compression.…”
Section: Discussionmentioning
confidence: 99%
“…However, as estimated by World Health Organization (in 2010, in international dollars [int$]) the cost per inpatient bed day may range from 234.7 to 757.5 int$ in European countries to 646.5 to 1093.5 int$ in USA and Canada 19 . A previous study on a sample from an USA hospital found costs associated with orthosis that ranged from about $7000 to 13000, including hospitalization until the orthosis was fitted 20 …”
Section: Discussionmentioning
confidence: 99%
“…19 A previous study on a sample from an USA hospital found costs associated with orthosis that ranged from about $7000 to 13000, including hospitalization until the orthosis was fitted. 20 Apart from the costs associated with hospitalization, the cost of the device itself was also significantly higher in inpatients compared with outpatients. This may be associated with the fact that inpatients receive custom-made orthosis, significantly more expensive than prefabricated ones.…”
Section: Orthosis Costsmentioning
confidence: 99%
“…[14][15][16][17] While the costs of TLSOs vary, even the most expensive (custom-made) braces typically cost less than $5,000, with lifetime costs of bracing treatment estimated to be less than $65,000, or roughly a third of the cost of surgery. [18][19][20] Avoiding spinal fusion by early AIS identification and appropriate treatment with a TLSO brace is advantageous to both the patient and healthcare systems.…”
Section: Key Conceptsmentioning
confidence: 99%